Analisis Tingkat Kematangan Adopsi Service Oriented Architecture Menggunakan ISO/IEC 16680 (OSIMM) - Mutiah, Nurul; Febriyanto, Ferdy (JSINBIS (Jurnal Sistem Informasi Bisnis), 2021)
Enterprise application integration makes data sharing easier, efficient and provides flexibility for organizations to seize opportunities and respond to stakeholder needs. Faculty of Mathematics and Natural Sciences (FMIPA) Tanjungpura University is an organization that wants to apply information technology effectively to support its business processes. Currently the application at FMIPA is built with different platforms and databases so that it cannot be integrated to share data between parts of the organization. FMIPA intends to build a service-oriented technology architecture to support the realization of organizational goals. SOA (Service Oriented Architecture) can be used as a framework for enterprise application integration. SOA adoption is often not as expected because organizations do not plan their processes comprehensively. It is necessary to measure the maturity level of the organization's SOA adoption so that the current state of the organization's SOA and future expectations can be found. ISO/IEC 16680 (OSIMM) is a method for measuring the SOA maturity level with 7 levels of maturity and 7 dimensions. To expedite the SOA adoption process in FMIPA, SOA maturity level was measured using ISO/IEC 16680. Based on measurements of the seven dimensions of SOA at ISO/IEC 16680, it was found that the current level of SOA adoption maturity (As-Is) at FMIPA Untan was at the level one (Silo), while the expected maturity level (To-Be) is level four (Service). Gap analysis then carried out related to the gap in maturity levels, and is followed by making recommendations dan roadmap for SOA adoption.